Using humour to reduce anxiety and improve performance in a college ESP classroom centre / Syahrin Baharom Shah - Baharom Shah, Syahrin (2007)
Recent studies in second language acquisition highlight the importance of language play (LP) in the development of competence in the target language. Humour based language plays were sometimes used by teachers in the classroom to promote student to talk and participate in the classroom activities, due to the beliefs that humour can make learning fun and reduce students' interaction and communication anxiety. In this study, seventeen college students took the Foreign Language Classroom Anxiety Scale and the State Trait Anxiety Inventory (A-State) to measure the cause of their classroom anxiety and their response to the humour-focused language activity. Both pretest and post-test were used to measure the possible effect of reduced anxiety on the students' performance. Analysis of the results of the study suggested the possibility that the students' anxiety level was reduced after the language play activity. The students' performance however, does not seem to be strongly affected by the reduced level of anxiety.